La necesidad de la atención a la diversidad cultural desde las instituciones educativas colombianas - Ruiz Cerquera, María Alejandra; Álvarez Díaz, Mayda Bárbara (Revista Conrado, 2020)
Las instituciones educativas presentan un perfil cada vez más plural desde el aspecto cultural; así mismo están en un contexto social culturalmente diverso el cual está sometido a profundos cambios en el comportamiento interpersonal y las relaciones que se establecen entre individuos de diferentes culturas. Es por tanto una necesidad imperiosa que desde las instituciones educativas se diseñen y apliquen estrategias de aprendizaje colaborativo en la asignatura de informática, que contengan elementos importantes como el reconocimiento, el autoreconocimiento y el respeto a las diferentes culturas presentes en el aula de clases. Se considera que se debe propiciar una educación en la que se respete la diversidad, se promocione la convivencia intercultural y se rechace todo tipo de exclusión social, ya sea por motivos de etnia o de cultura, de ahí la necesidad de desarrollar nuevas formas que permitan el aprendizaje colaborativo en la asignatura informática. Palabras clave: Diversidad, aula de clase, enseñanza, estrategia, informática, aprendizaje colaborativo. ABSTRACT We currently live in a society in which technological advances and forms of social relations confront us with new challenges due to the new transformations that are constantly occurring in interpersonal relations, the workplace, and consequently the school as an educational institution, a very important component in society, because it is from there that the principal processes of learning, of plurality of identities, and of cultural expressions of the peoples and communities that make up the nation are developed. Educational institutions present an increasingly plural profile from the cultural aspect; they are also in a culturally diverse social context that is subject to profound changes in interpersonal behaviour and in the relations that are established between individuals of different cultures. It is therefore imperative that educational institutions design and implement collaborative learning strategies in the field of computer science, which contain important elements such as recognition, self-recognition and respect for different cultures present in the classroom. It is considered that an education in which diversity is respected, intercultural coexistence is promoted and all types of social exclusion are rejected, whether for reasons of ethnicity or culture. Keywords: Diversity, classroom, teaching, strategy, computing, collaborative learning.